Third World Revolutionary Projects and the End of the Cold War - Rocamora, Joel (Kasarinlan: Philippine Journal of Third World Studies; Vol 6 No 4 (1991), 2008)
Third World liberation movements are very much alive. These struggles are in fact intensifying as political and economic conditions deteriorate. While the decade of the '80s did not produce as many successful revolutions as the '70s, the victory in Namibia and advances in the struggles in South Africa and El Salvador provide a sense of continuing forward movement. These movements are still mainly Marxist in orientation. Marxism remains the preferred tool of political and economic analysis. But the alternative futures proffered and the strategy and tactics applied are very diverse. They range from mass movement-based, electoral tactics of the Partido dos Trabalhadores (the PT or Workers' Party) of Brazil to the underground guerill strategy of the National Democratic Front in the Philippines. Intense debate within these movements provide the base for this creative and dynamic diversity.